The Multi Layer Structure of Inequality - Talmud, Ilan (Hagar: Studies in Society and Culture, 2001)
The article discusses the multi layer structure of inequality. The author stated that the first layer is a naive one, that inequality is observed through differential capacities of social actors. The second is structural, where social structure systematically gains certain players at the expense of others. The third is a narrative one, where social construction and negotiation of reality delineate who takes what piece of the pie. Moreover, the author discussed the relationship between inequality and heterogeneity and global trade networks.